Cigarette and e-cigarette reversely regulated autophagy via distinct level of ROS in vitro - Yao Wang; Jialing Zhong; Zuyi Jin; An Luo; Zehong Wu; Xingtao Jiang; Jianwen Chen; Peiqing Liu; Min Li (Ecotoxicology and Environmental Safety)
With the increasing prevalence of e-cigarettes, a systematic evaluation of the cytotoxicity among the components of e-cigarettes is needed. This study aimed to compare the cytotoxicity of conventional cigarettes and e-cigarettes, identify the toxic components of e-cigarettes, and explore the mechanisms of cellular injury. In this study, the conventional cigarette and seven flavored e-cigarettes, along with their constituents, including solvents, nicotine, and seven flavoring agents were tested. The Cambridge filter pad method was employed to collect conventional cigarettes smoke condensate (CSC) and e-cigarettes aerosol condensate (EAC). CCK-8 assays were used to assess their cytotoxicity on respiratory system-related cells and cardiovascular-related cells. The findings revealed significantly higher cytotoxicity in CSC compared to EACs, with EACs exhibiting IC50 values at least 12 times higher across various flavors and cell lines. Notably, among the seven flavors, the Cola-flavored EAC exhibited the most pronounced cytotoxicity, with flavoring agents identified as the primary contributors to the cytotoxicity of e-cigarettes. Furthermore, noteworthy differences in cellular mechanisms were observed between CSC and EAC-Cola in BEAS-2B cells, particularly in terms of ROS level and autophagy regulation. CSC induced approximately 10 times higher levels of ROS compared to EAC. Due to the distinct level of ROS, CSC significantly inhibited autophagy while EAC induced autophagy. Scavenge of ROS clearly eliminates the autophagy modulated by both CSC and EAC. These findings contribute to a comprehensive understanding of the cytotoxicity of e-cigarettes and conventional cigarettes, providing a scientific basis for health risk assessment and regulatory mechanisms.